Cane molasses and oligofructose in the diet of laying hens improves the mineral content of eggs and meat - Gultemirian, María de Lourdes; Iglesias, Bernardo Fabricio; Perez Chaia, Adriana; Apella, María Cristina (Elsevier, 2022)
Poultry-based foods contribute to human health due to their high nutrient value. Previously, it was shown that short-chain fatty acids (SCFAs) produced by in vitro intestinal fermentation of a molasses and oligofructose mixture (M-O) stimulated iron and calcium transport through the colonic epithelium of laying hens. However, the real impact of including M-O mixture in the diet on the mineral content of poultry products had not yet been demonstrated. In this study, Hy-Line W-36 leghorn hens were assigned into two groups that either received a conventional diet or a diet supplemented with cane molasse and oligofructose, over a period of 42 days. The weight of the animals and their eggs, blood parameters and intestinal epithelium integrity were determined. Intestinal bacteria, their fermentation products, and the mineral content of eggs, bones and muscles were also assessed. The experimental diet proved to be safe, favored the proliferation of SCFA producing bacteria in the intestines, led to higher concentration of acids (mainly SCFA) in the digesta, and induced the elongation of microvilli at the apical tip of enterocytes. Mineral content of eggs and meat were improved after four weeks of feeding with the experimental diet compared to the conventional one. Higher iron content was observed in the edible portion of eggs and leg muscle, and higher calcium content was observed in the egg edible portion and shell in hens fed the supplemented diet. This feeding strategy could be useful to improve the mineral content of poultry products and therefore human nutrition, while diversifying molasses applications.